Relationship Between Emotional Intelligence and Learning - Saharudin Saharudin (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study is a correlational research that aims to find the relationship between emotional intelligence and learning motivation with English writing skills description paragraph. This study used survey method with correlation with the number of 105 students in MTs and equal Classes VII District of East Praya, Central Lombok, West Nusa Tenggara province and selected randomly. Instrument in the form of questionnaires and tests validated through testing expertise and the calculation of Pearson Product Moment and reliability testing done using Cronbach Alpha. Verification of the hypothesis is done by regression analysis and found the regression model, and the correlation coefficient between emotional intelligence, learning motivation with English writing skills description paragraph. The results showed that the relationship between emotional intelligence with English writing skills description paragraph is .341 (α .05). The relationship between learning motivation and English writing skills description paragraph is .153 (α, .05). Found a correlation coefficient of emotional intelligence and learning motivation with English writing skills description paragraph is .580 (α, .05). Based on these results it can be concluded that English writing skills description paragraph can be influenced by emotional intelligence and students' learning motivation.